Análisis de las estrategias de comercialización de la Empresa Agro Mat. - Melendrez Jiménez, Anderson Hernán (2022)
This research work aims to analyze the marketing strategy that the company Agro Max has to position itself in the local market; the line of research is Information and Communication System, Entrepreneurship and Innovation and as a sub-line marketing and commercialization; In addition to the contribution of the descriptive method and the qualitative research method, which helped to interpret and understand the various situations that arise in the company chosen to carry out the study, the techniques applied to obtain the information were interviews directed to the manager of the company. company and the surveys carried out on customers, which resulted in the company's main problem being the lack of application of marketing specifically, of a strategic nature, so that it does not generate a competitive advantage based on the strengths and opportunities , on the other hand, direct the corresponding actions to reduce the negative aspects, that is, lacking an analysis of the market and consumer behavior, the perspective of the client is not considered to generate viable strategies that generate satisfaction of the needs, on the other hand , it does not use any marketing method due to ignorance about e the importance of implementing marketing strategies related to marketing and have affected their level of sales.